A case of Bardet‑Biedl syndrome caused by a recurrent variant in BBS12: A case report. Issue 6 (29th September 2021) - FOCȘA, INA OFELIA; BUDIȘTEANU‑, MAGDALENA; BURLOIU, CARMEN; KHAN, SHERAZ; ,; SADEGHPOUR, AZITA; ,; BOHÎLȚEA, LAURENȚIU C.; DAVIS, ERICA E.; BĂLGRĂDEAN, MIHAELA
No abstract available